Comparative efficacy and safety of mycophenolate mofetil and azathioprine in combination with corticosteroids in the treatment of lymphocytic myocarditis - R. S. Rud; O. V. Blagova; E. A. Kogan; V. M. Novosadov; A. Yu. Zaitsev; V. P. Sedov; V. A. Zaydenov; A. G. Kupriyanova; V. V. Kadochnikova; A. E. Donnikov; A. V. Nedostup (Российский кардиологический журнал)
Aim. To study the efficacy and safety of mycophenolate mofetil (MM) in combination with corticosteroids in the treatment of lymphocytic myocarditis in comparison with a standard combination of corticosteroids and azathioprine.Material and methods. The study included 46 patients aged 18 years and older with severe and moderate lymphocytic myocarditis (men, 34; women 12; mean age, 53,5±13,0 years). The diagnosis was verified using endomyocardial biopsy. Symptom duration averaged 9,5 [4; 20.25] months. All patients had class 3 [2,75; 3] heart failure (HF). The main group included 29 patients who received MM 2 g/day, including six patients — instead of azathioprine, which was canceled due to cytopenia (n=3) or insufficient effect (n=3). The comparison group included 17 patients who received azathioprine 150 [100; 150] mg/day. Patients of both groups also received methylprednisolone at a starting dose of 24 [24; 32] and 24 [24; 24] mg/day and standard HF therapy. In 7/2 patients, the parvovirus B19 genome was detected in the myocardium. In all cases, an increase in anticardiac antibody titers was evidence of immune activity. The average follow-up period was 24 [12; 54] months (at least 6 months).Results. The groups were completely comparable in age, initial characteristics and standard drug therapy. In both groups, a comparable significant increase in the ejection fraction (EF) was noted as follows: from 31,2±7,6 to 44,7±8,3% and from 29±9,1 to 46±11,9% (p<0,001). An excellent response to treatment (an increase in EF by 10% or more) was noted in 68,2% and 66,7% of patients, a good response (by 9-5%) — in 27,3% and 14,3%, a poor response (an increase in less than 5% or a decrease in EF) — in 4,5% and 19,0%, respectively. In both groups, we noted the same significant (p<0,01) decrease in pulmonary artery systolic pressure (36,3±12 to 28,1±6,1 mm Hg in the MM group and from 44,1±8,5 to 30,7±12,1 mm Hg in the azathioprine group), left ventricular (LV) end-diastolic dimension (from 6,4±0,6 to 6±0,7 cm and from 6,2±0,5 to 5,8±0,6 cm), LV end-diastolic volume (from 188,7±55,2 to 178,8±57,1 ml and from 167,8±47,5 to 163,3±61,8 ml), LV end-systolic volume (from 130,3±44,1 to 98,4±32 ml and from 118,1±39 to 94,1±46 ml), left atrial volume (from 98,3±30,3 to 86,7±32,6 ml and from 105±27,4 to 91,2±47,3 ml, p<0,05), as well as mitral regurgitation grade. The incidence of deaths was 2 (6,9%) and 2 (8,7%), transplantation — 1 (3,4%) and 1 (4,3%) patients, death+transplantation end point — 3 (10,3%) and 2 (11,8%) without significant differences between the groups. The presence of the parvovirus B19 genome did not affect the results of treatment. The incidence of infectious complications was comparable in both groups (in one case, MM was completely canceled), no new cytopenia cases were noted during the follow-up period.Conclusion. In patients with moderate and severe virus-negative (except for parvovirus B19) lymphocytic myocarditis, the combination of moderate-dose corticosteroids with mycophenolate mofetil 2 g/day is at least no less effective than the standard regimen of immunosuppressive therapy. There was a tendency towards a more pronounced decrease in anticardiac antibody titers in combination with better tolerance (no cases of cytopenia) in MM group. MM in combination with corticosteroids can be recommended as an alternative treatment regimen for lymphocytic myocarditis.